PLN CSR Program Through Community Empowerment at Saguling Dam, Citarum River, Bandung, West Java - Gan Gan Giantika; Siti Qona’ah (Manunggal Halim Jaya, 2024)
Saguling Dam is a man-made reservoir located in West Bandung Regency, which dams the flow of the Citarum River, the largest river in West Java. The current condition of the dam has been heavily polluted by an abundance of water hyacinth and a buildup of household waste covering the river's surface. According to data from the Bandung City Sanitation Company in 2016, approximately 2.5 million residents produced 1,500 - 1,600 tons of waste per day. However, only 1,100 - 1,200 tons were transported to the Sarimukti Final Disposal Site (TPA), and 150 - 250 tons were processed by residents. The remaining 150 - 250 tons of waste were disposed of in Citarum River's tributaries. PLN (State Electricity Company) implemented a Corporate Social Responsibility (CSR) program themed